The Accounting Equation Revisited: A Conceptual Accounting Model. - Nicol, Robert E. C. (The Accounting Review, 1968)
Abstract This article focuses primarily to matters related to the teaching of accounting. The traditional accounting equation has, for many years, served as the fundamental identity in teaching introductory accounting courses. Many teachers employ this equation in varying degrees of extension, to conceptualize the accounting system, and in particular, to establish the relevant relationships between transactions, accounts, debit and credit entries, and the end product of the accounting process the financial statements. The author hopes to show in this article that, with very little effort and difficulty, the traditional approach may be extended so as to include the derivation of the financial statements themselves, within the equational schema. This allows a very complete and simple model of the whole accounting process, and one to which, in the author's experience, beginning students are quite receptive. The number of students who have retained this initial model and subsequently commented upon its relevance to more advanced work, particularly in designing computerized accounting systems, has confirmed its utility.